9-3y=5y+5
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 20:26:44
9-3y=5y+59-3y=5y+59-3y=5y+59-5=5y+3yy=0.5移项得:9-5=5Y+3Y4=8YY=1/2移项得:9-5=5Y+3Y4=8YY=1/2-3y-5y=5-9-8y=-
9-3y=5y+5
9-3y=5y+5
9-3y=5y+5
9-5=5y+3y
y=0.5
移项得:9-5=5Y+3Y
4=8Y
Y=1/2
移项得:9-5=5Y+3Y
4=8Y
Y=1/2
-3y-5y=5-9 -8y=-4 y=1/2
解:-8Y=-4
Y=0.5
9-3y=5y+5
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
y(y-2)²-y(y+3)(y-5) y=1/2 化简求值
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
(5y+1)+ (1-y)= (9y+1)+ (1-3y);
(5y+1)+ (1-y)= (9y+1)+ (1-3y);
[T,Y]=ode45(@rigid,[0 1],[rand(15,1)]);plot(T,Y(:,1),'-',T,Y(:,2),'-.',T,Y(:,3),'.',T,Y(:,4),'-',T,Y(:,5),'-.',T,Y(:,6),'.',T,Y(:,7),'-',T,Y(:,8),'-.',T,Y(:,9),'.',T,Y(:,10),'-',T,Y(:,11),'-.',T,Y(:,12),'-.',T,Y(:,13),'.',T,Y(:,14),'-',T,Y(:,15),'.')
(x+y-5)*(x+y-5)+(x-y+3)=0 x*x-y*y
2y+5/3y-6-y/2=5y-4/2y-4
2(y-4)(3y+2)-5(-3y+7)(y+1),其中y=-1
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程:3y²-(2y+1)(y-2)=(y-5)(y+1)
已知:3x-5y=0,求x/y,x-y/y,x-y/x
8y-4=12-5y+9y
3(y-3)-5(1+y)=7(y-1)
2(3-2y)+3y =5求y